Design of a compact dual‐band monopole antenna using a top‐loaded octagon patch and perforated shorting pin. Issue 6 (24th April 2018) - Park, Jae Sung; Choi, Hak Keun
Abstract: In this article, an antenna operated in the dual band (824‐894 and 1750–2800 MHz) is proposed, and its performance is verified. The proposed antenna is structured with a monopole antenna of a reversed crossing trapezoidal type, over which a top‐loaded octagon patch is added; moreover, a perforated shorting pin is appended to the center of the reversed crossing trapezoidal monopole antenna. The performance is verified while changing the width at the connector between the top‐loaded octagon patch and reversed crossing trapezoidal monopole antenna and the width of the inverted‐L slit width after inserting it between the reversed crossing trapezoidal monopole antenna and the top‐loaded octagon patch. The monopole antenna of the crossed reversed crossing trapezoidal type has a broadband characteristic at the 1750‐ to 2800‐MHz band and can be run even in the 824‐ to 894‐MHz band by adding the top‐loaded octagon patch and perforated shorting pin. The antenna proposed in this study is a low‐profile antenna with a height of ∼λ/7 in the 824‐ to 894‐MHz (center frequency: 859 MHz) band, and it satisfies a return loss below −14 dB. The band characteristic at 1750–2800 MHz satisfies a return loss below −14 dB, even if the structure for the 824‐ to 894‐MHz band is added. The antenna gain is revealed as ∼−1 to 1 dBi in the 824‐ to 894‐MHz band.